Digital Upskilling and Reskilling for Smart Manufacturing Workforce: A Bibliometric Analysis (2020–2025) - Mohammad Kartika; Gani Ramdani; Malvin Dharma Pradipta; Arief Noviarkahman Zagladi; Elvira Nora (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Industry 4.0 and smart manufacturing paradigms have fundamentally altered the skill profiles required of the industrial workforce. Consequently, digital upskilling and reskilling have become paramount strategies within human resource development (HRD). Despite increasing academic attention, the literature lacks a comprehensive bibliometric evaluation of these digital training initiatives specifically tailored to smart manufacturing environments. To address this void, the present study conducts a bibliometric review of Scopus-indexed literature from 2020 to 2025. Through VOSviewer software, we analyze publication trajectories, influential contributors, primary publication outlets, citation impacts, and thematic networks. The results demonstrate an accelerated publication rate post-2020, converging around four primary clusters: Industry 4.0 competency frameworks, digital training infrastructures, workforce adaptability, and continuous learning. This analysis not only delineates a roadmap for future academic inquiry but also provides strategic guidance for HRD practitioners managing industrial transitions.